FORMATION OF ACCOUNTING AND ANALYTICAL INFORMATION OF THE MUNICIPAL COMPANY ON ACCOUNTS RECEIVABLE AND PAYABLE IN THE CONTEXT OF ENSURING BUSINESS COMMUNICATION (INNOVATIVE ECONOMY, 2019)
Yakymova L.P., Karielova O.V. FORMATION OF ACCOUNTING AND ANALYTICAL INFORMATION OF THE MUNICIPAL COMPANY ON ACCOUNTS RECEIVABLE AND PAYABLE IN THE CONTEXT OF ENSURING BUSINESS COMMUNICATIONPurpose. The aim of this article is to substantiate of methodical approaches to formation of accounting and analytical information concerning accounts receivable and payable in the context of ensuring business communication of the municipal company.Methodology of research. General scientific and special methods of cognition are used in the research process, in particular: methods of theoretical generalization and comparative analysis – for the analysis of scientific works and practical experience of improvement of communications in accounting; system approach, methods of analysis and synthesis – for substantiation of methodical approaches and suggestions for the formation of accounting and analytical information; methods of econometric modeling – for the construction of a model of net profit of municipal companies.Findings. The relationship between the problems of accounting for accounts receivable and payable and the principles of business communications are established. Changes in the financial statements of municipal companies, which are consistent with the principles of effective communication and improve the information of internal and external users on accounts receivable and payable and their impact on the financial stability of the company, are proposed.Originality. Methodical approaches to restructuring of notes to financial statements in terms of accounts receivable and payable are substantiated, which, in contrast to the existing ones, provides improved communication in financial statements of municipal companies.Practical value. Theoretical and methodical provisions of the research are brought to the level of specific proposals for the formation of accounting and analytical information on accounts receivable and payable of the municipal company.Key words: financial statements; accounts receivable; accounts payable; communications; municipal company; model.
Keywords: Key words; financial statements; accounts receivable; accounts payable; communications; municipal company; model.